2015
DOI: 10.1007/s12190-015-0877-7
|View full text |Cite
|
Sign up to set email alerts
|

Similarity-based minimization of fuzzy tree automata

Abstract: This paper presents a contribution to the problem of similarity-based minimization of deterministic fuzzy finite tree automata (DFFTA). The main question is: how to minimize the number of states of a complete and reduced DFFTA such that the languages of the original automaton and the minimized one be similar but not necessarily equal? Based on extended concepts of fuzzy distance and similarity measures on L-fuzzy sets, we introduce the notion of similarity-based minimal (s-minimal) DFFTA which approximately ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The bisimulation relation models equivalence between states of nondeterministic automata [45]. The equivalence relation between states of an automaton is done to minimize the automaton, and the equivalence relation between states of two automata is usually done for comparing their behaviors [13,14,32].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The bisimulation relation models equivalence between states of nondeterministic automata [45]. The equivalence relation between states of an automaton is done to minimize the automaton, and the equivalence relation between states of two automata is usually done for comparing their behaviors [13,14,32].…”
Section: Related Workmentioning
confidence: 99%
“…Our definitions in this section, are borrowed from [7,32,33]. The set of natural numbers (including zero) is denoted by N. A Σ-alphabet is a finite and nonempty set of symbols.…”
Section: Ranked Alphabet and Fuzzy Tree Automatamentioning
confidence: 99%
See 2 more Smart Citations
“…Bozapalidis and Bozapalidoy [3] showed that linear tree homomorphisms preserve syntactic recognizability. More results on fuzzy tree automata can be found in [24,26,39] and references therein. Since, fuzzy tree automata take values in the unit interval [0, 1], to enhance the processing ability of fuzzy tree automata, Ghorani and Zahedi [20][21][22], Ghorani et al [23] and Ghorani [18,19] extended the membership value to a more general algebraic structure and considered tree automata based on complete residuated lattice-valued logic.…”
Section: Introductionmentioning
confidence: 99%